Experimental Investigation on Propagation Behavior of Hydraulic Fractures in Coal Seam during Refracturing - Xun Sun; Shicheng Zhang; Xinfang Ma; Yushi Zou; Guanyu Lin (Geofluids)
Refracturing is an effective technology for reinstituting a percolation path and improving the fracture conductivity in coal measure strata. Hydraulic fracture (HF) propagation is complicated due to the presence of cleats and stress change caused by pore pressure changes. Many scholars have studied HF propagation in the initial fracturing of coal, but the refracturing in coal seams is rarely mentioned. In this study, laboratory refracturing experiments were conducted on large natural coal specimens under various triaxial stress states to investigate the propagation of HFs in coal seams. The mechanical properties of coal were tested before refracturing. The maximum and the minimum horizontal principal stresses are inverted to simulate the stress change caused by the production and pore pressure reduction of the stress condition after initial fracturing. Experimental results showed three different types of HF initiation and propagation during refracturing: (1) under low horizontal stress differences (0-2 MPa), HF propagated along the cleats, and no new HFs were formed on the walls of the initial HFs regardless of changes in the horizontal stress; (2) under high horizontal stress differences (4–8 MPa) with no stress inversion, a major HF was initiated parallel to the orientation of maximum horizontal stress during initial fracturing; new branches propagated along cleats in the orientation of the minimum horizontal stress during refracturing; and (3) under high horizontal stress differences (4–8 MPa) with maximum and minimum horizontal stress inversions, the main HF formed along the orientation of the maximum horizontal stress, and a new HF perpendicular to the initial HF was formed during refracturing. Multiple factors affect fracture morphology during refracturing. Cleats affect the HF growth path and the creation of new branches. The in situ stress determines the initiation and propagation of new HFs.